Preparation and Characterization of New (Halogenated Azo-Schiff) Ligands with Some of their Transition Metal Ions Complexes - Kadhim, Sroor M.; Mahdi, Saad M. (Iraqi Journal of Science, 2022)
Two new halogenated azo-Schiff ligands were prepared in two steps. The first step included a condensation between 4-amino acetophenone and 2-fluoro-4-bromo aniline to give the corresponding Schiff base. In the second step, the diazonium salt of this Schiff base reacted with 2-naphthol and 4,5-diphenylimidazole to form two new azo-Schiff base derivatives as ligands; (3-((E)-(4-((E)-1-((4-bromo-2-fluorophenyl) imino)ethyl) phenyl) diazenyl) naphthalen-2-ol (HSBAN) (L1) and ((E)-N-(4-bromo-2-fluorophenyl)-1-(4-((E)-(4,5-diphenyl-1H-imidazol-2-yl)diazenyl) phenyl) ethan-1-imine) (HSBAI) (L2), respectively. These new ligands were characterized by mass spectrometry, FT-IR, 1H NMR, UV-Visible spectroscopy and elemental microanalysis (CHN). Five divalent transition metal ion complexes (Co, Ni, Cu, Cd, and Hg) were prepared and characterized, beyond the determination of the optimal condition (concentration, pH value, and the mole ratio M:L) using UV-visible studies. Additionally, complementary techniques, such as atomic absorption, electrical conductivity and magnetic susceptibility, were performed to deduce their geometries. The comprehensive study suggested an octahedral geometry for all complexes except Cd and Hg complexes of the first ligand.